Defining early education quality using CLASS-observed teacher-student interaction - Pianta, Robert C.; Hofkens, Tara (Frontiers in Psychology, 2023)
In this paper we argue that the quality of early education programs or classrooms can be defined in terms of features of teachers’ interactions with students observed using the Classroom Assessment Scoring System, or CLASS. We present evidence suggesting that dimensions of teacher-student interactions can be described, observed, and measured consistently across cultures and countries and that such dimensions also have modestly positive influence student development and learning. Evidence is summarized indicating that interactions can also be improved systematically through professional development interventions. The paper relies on a framework that describes core features of effective teacher-student interactions present across countries’ highly varied settings and cultural contexts. Limitations of the study include exclusive reliance on the CLASS and that most countries were not low or middle income. We discuss the cross-cultural applicability of the framework and outline suggestions for education policy and practice and future directions for research.